استخدام وسائط كاهوت لتحسين إتقان المفردات العربية لطلاب الصف الخامس في المدرسة الإبتدائية الإسلامية الزهرة - Nur Mazidah; Muhammad Thohir (UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to explain the use of the online game-based Kahoot platform that is used to improve vocabulary mastery in learning Arabic. This study uses the method of classroom action research (CAR) using the Kemmis & McTaggart model with four stages, namely planning, carrying out an action, observation or observation, and reflection, with the design used in this study on two cycles, each cycle contains two cycles. Four stages, namely: 1) planning, 2) carrying out actions, 3) observing or observing, 4) thinking. The results obtained are that the use of the online gaming platform Kahoot can facilitate students to improve vocabulary mastery in Arabic The research conducted in the first course and the second course in the fifth semester SDI Az-Zahro Gresik shows that there is an increase in the Arabic vocabulary learning outcomes in Kahoot media application where the average number of student success results in the first cycle is 70% and the results in the second cycle rise to 87%.